Essentials of operations on files and directories in teaching - Dagys, Viktoras; Grigas, Gintautas (Lietuvos matematikos rinkinys, 1999)
The transition towards more sofisticated knowledge of data classification, arrangement, coding, and processing at the level of files and directories may be achieved by means of separation goals from tools and concentration on goals. So the tool must be simple to learn and universal to cover all desired goals. The Windows Commander was used as a tool for discussion.